2016
DOI: 10.5325/transportationj.55.2.0190
|View full text |Cite
|
Sign up to set email alerts
|

Weatherproofing Supply Chains: Enable Intelligent Preparedness with Data Analytics

Abstract: Catastrophic events, occurrences of severe weather, and year-over-year changes in the weather pose various degrees of risks for companies and their supply chains. These risks range from severe, prolonged supply chain disruptions, to critical stockouts, and to escalating costs due to last-minute implementation of the emergency procedures. When these risks come to fruition, the financial impacts can easily reach millions of dollars or more. This study introduces a new concept of intelligent preparedness—prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Zagorecki, Johnson, and Ristvej (2013) review the use of data mining and machine learning in disaster management applications. Coyle, Ruamsook, and Symon (2016) note the need for intelligent preparedness to sense, capture, and analyze data (specifically weather) in disaster management, providing a case demonstration. Papadopoulos et al.…”
Section: Application Fieldsmentioning
confidence: 99%
“…Zagorecki, Johnson, and Ristvej (2013) review the use of data mining and machine learning in disaster management applications. Coyle, Ruamsook, and Symon (2016) note the need for intelligent preparedness to sense, capture, and analyze data (specifically weather) in disaster management, providing a case demonstration. Papadopoulos et al.…”
Section: Application Fieldsmentioning
confidence: 99%
“…The obtained results and study focus of big data with the DSS in performance measurement can be used for continuous improvement in forecasting demands, predicting purchasing needs, decreasing lead times, minimising production wastes, controlling inventory and stock outs. Coyle et al (2016) also found that big data can be used for predicting weather events, making better decision making and implementing operations-related strategies after a disaster. Costs are directly reduced.…”
Section: Introductionmentioning
confidence: 99%